Nutrient contents and efficiencies of beech and spruce saplings as influenced by competition and O₃/CO₂ regime - Rodenkirchen, Hermann; Göttlein, Axel; Kozovits, Alessandra R; Matyssek, Rainer; Grams, Thorsten E. E (European journal of forest research, 2009)
Saplings of Fagus sylvatica and Picea abies were grown under conditions of intra and interspecific competition in a 2-year phytotron study under combinations of ambient and elevated ozone (+O₃ which is 2 x O₃, but <150 nl l⁻¹) as well as carbon dioxide concentrations (+CO₂ which is amb. CO₂ + 300 μl CO₂ l⁻¹) in a full factorial design. Saplings were analysed for various mineral nutrients in different plant organs as well as biomass production and crown development. The study was based on the assumption that nutritional parameters important for growth and competitiveness are affected by stress defence under limiting nutrient supply. The hypotheses tested were (1) that nutrient uptake-related parameters (a) as well as efficiencies in nutrient use for above-ground competition (b) of beech rather than spruce are impaired by the exposure to elevated O₃ concentrations, (2) that the efficiency in nutrient uptake of spruce is enhanced by elevated CO₂ concentrations in mixed culture, and (3) that the ability to occupy above-ground space at low nutrient cost is co-determinant for the competitive success in mixed culture. Clear nitrogen deficiencies were indicated for both species during the 2-year phytotron study, although foliar nitrogen-biomass relationships were not so close for spruce than for beech. O₃ stress did not impair nutrient uptake-related parameters of beech; thus hypothesis (1a). was not supported. A negative effect of elevated O₃ (under amb. CO₂) on the N and P based efficiencies in above-ground space occupation (i.e. lower crown volume per unit of N or P invested in stems, limbs and foliage) of beech supported hypothesis (1b). It appeared that ozone stress triggered a nutrient demand for stress defence and tolerance at the expense of above-ground competition (trade-off). Crown volume of beech under O₃ stress was stabilized in monoculture by increased nutrient uptake. In general, the +CO₂-treatment was able to counteract the impacts of 2 x O₃. Elevated CO₂ caused lower N and S concentrations in current-year foliage of both tree species, slightly higher macronutrient amounts in the root biomass of spruce, but did not increase the efficiencies in nutrient uptake of spruce in mixed culture. Therefore hypothesis (2) was not supported. At the end of the experiment spruce turned out to be the stronger competitor in mixed culture as displayed by its higher total shoot biomass and crown volume. The amounts of macronutrients in the above-ground biomass of spruce individuals in mixed culture distinctly exceeded those of beech, which had been strongly reduced by interspecific competition. The superior competitiveness of spruce was related to higher N and P-based efficiencies in above-ground space occupation as suggested in hypothesis (3).